2010
DOI: 10.2489/jswc.65.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Livestock grazing and vegetative filter strip buffer effects on runoff sediment, nitrate, and phosphorus losses

Abstract: Livestock grazing in the Midwestern United States can result in significant levels of runoff sediment and nutrient losses to surface water resources. Some of these contaminants can increase stream eutrophication and are suspected of contributing to hypoxic conditions in the Gulf of Mexico. This research quantified effects of livestock grazing management practices and vegetative filter strip buffers on runoff depth and mass losses of total solids, nitrate-nitrogen (NO 3 -N), and ortho-phosphorus (PO 4 -P) under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…The increase of riparian zones along all streams can be possible mitigation option to buffer contaminants entering via surface runoff from farmland and ameliorate water quality impacts resulting from increased fertilizer application (Johnes and Heathwaite, 1997;Webber et al, 2010Lal et al 2011. Since riparian zones are prominently located between terrestrial and aquatic ecosystems, riparian processing of nutrients is very effective despite occupying a small area of land relative to the entire catchment.…”
Section: Watershed-based Mitigation Optionsmentioning
confidence: 99%
“…The increase of riparian zones along all streams can be possible mitigation option to buffer contaminants entering via surface runoff from farmland and ameliorate water quality impacts resulting from increased fertilizer application (Johnes and Heathwaite, 1997;Webber et al, 2010Lal et al 2011. Since riparian zones are prominently located between terrestrial and aquatic ecosystems, riparian processing of nutrients is very effective despite occupying a small area of land relative to the entire catchment.…”
Section: Watershed-based Mitigation Optionsmentioning
confidence: 99%
“…Different approaches to mitigate animal waste problems were adopted in the Rural Clean Water Program (RCWP) projects conducted in the American states of Utah and Florida due to their different climatic characteristics [2]. Multiple BMPs are usually combined together in a watershed, such as tillage and nutrient management practices [3] or grazing management and vegetative buffers [4] to effectively control pollutants from various sources. When numerous BMP options are available, whether various combinations of BMPs work synergistically or cancel the effect of each other when implemented together in a watershed must be evaluated [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, studies have shown high nutrient levels in runoff from horse paddocks and pastures grazed at high stocking rates (Airaksinen et al 2001;Parvage et al 2011). Moreover, livestock (cattle, horse, and sheep) manure often contains high levels of E. coli (Escherichia coli) (Weaver et al 2005), and livestock grazing, in general, causes nutrient runoff and the sedimentation of waterways (Webber et al 2010). Though individual small farms and rural residences have less of an individual impact on environmental quality than individual large farms, the overall impact of small-scale rural landowners grows as they increase in numbers and change land use patterns.…”
mentioning
confidence: 98%